A 24-h work shift in intensive care personnel: biological pathways between work stress and ill health - Matejovic, M; Chvojka, J; Sykora, R; Krouzecky, A; Radej, J; Parizkova, R; Dostal, P; Novak, I; Cerny, V (The Journal of international medical research, 2011)
This study evaluated inflammatory, coagulation and microvascular responses to a continuous 24-h work day in 13 healthy intensive care physicians. Inflammatory markers (interleukin [IL]-2, IL-6, IL-10, tumour necrosis factor-α, matrix metalloproteinase [MMP]-9 and adiponectin), adhesion molecules (vascular cellular adhesion molecule-1 and intercellular adhesion molecule-1 [ICAM-1]), coagulation parameters (thrombin-anti thrombin, von Willebrand factor and tissue factor) and sublingual micro circulation were assessed before and after a 24-h work shift. The 24-h work shift had no effect on inflammatory markers and ICAM-1. Direct visualization of micro-circulation did not reveal stress-related perfusion abnormalities. A 24-h work shift in the intensive care unit was associated with significantly increased plasma levels of tissue factor - a potentially important mechanism linking acute job strain, haemostasis and atherosclerosis. The long-term consequences warrant further evaluation.
Keywords: zdraví; hemostáza; Intensive Care Units; Endothelium, Vascular; mediátory zánětu; Time Factors; Stress, Physiological; mužské pohlaví; Biological Phenomena; Adult; fyziologický stres; Inflammation Mediators; Microcirculation; Health Personnel; ženské pohlaví; Thromboplastin; Humans; Hemodynamics; tkáňový faktor; biologické markery; jednotky intenzivní péče; hemodynamika; časové faktory; Hemostasis; biologické jevy; cévní endotel; Health; dospělí; Biomarkers; Female; mikrocirkulace; zdravotnický personál; lidé; Male